Home » Blog » Prove some properties of the complex sine and cosine functions

Prove some properties of the complex sine and cosine functions

The following definitions extend the sine and cosine functions to take arguments z \in \mathbb{C}:

    \[ \cos z = \frac{e^{iz} + e^{-iz}}{2}, \qquad \sin z = \frac{e^{iz} - e^{-iz}}{2i}. \]

Prove the following formulas, where u,v,z are complex numbers and z = x + iy.

  1. \sin (u+v) = \sin u \cos v + \cos u \sin v.
  2. \cos (u+v) = \cos u \cos v - \sin u \sin v.
  3. \sin^2 z + \cos^2 z = 1.
  4. \cos (iy) = \cosh y, \qquad \sin(iy) = i \sinh y.
  5. \cos z = \cos x \cosh y - i \sin x \sinh y.
  6. \sin z = \sin x \cosh y + i \cos x \sinh y.

  1. Proof. Using the given definition of the sine of complex numbers we have

        \begin{align*}  \sin (u+v) &= \frac{e^{i(u+v)} - e^{-i(u+v)}}{2i} \\[9pt]  &= \frac{e^{iu}e^{iv} - e^{-iu}e^{-iv}}{2i} \\[9pt]  &= \frac{2 e^{iu}e^{iv} - 2 e^{-iu}e^{-iv}}{2(2i)} \\[9pt]  &= \frac{2e^{iu}e^{iv} + e^{iu}e^{-iv} - e^{iu}e^{-iv} + e^{-iu}e^{iv} - e^{-iu}e^{iv} - 2e^{-iu}e^{-iv}}{2(2i)} \\[9pt]  &= \frac{e^{iu}(e^{iv} + e^{-iv}) - e^{-iu}(e^{iv} + e^{-iv}) + e^{iv}(e^{iu} + e^{-iu}) - e^{-iv}(e^{iu} + e^{-iv})}{2(2i)} \\[9pt]  &= \frac{(e^{iu} - e^{-iu})(e^{iv} + e^{-iv})}{2(2i)} + \frac{(e^{iv} - e^{-iv})(e^{iu} + e^{-iu})}{2(2i)} \\[9pt]  &= \sin u \cos v + \sin v \cos u. \qquad \blacksquare \end{align*}

  2. Proof. Similar to part (a) we compute

        \begin{align*}  \cos (u+v) &= \frac{1}{2} \big( e^{i(u+v)} + e^{-i(u+v)} \big) \\[9pt]  &= \frac{1}{2} \big( e^{iu} e^{iv} + e^{-iu} e^{-iv} \big) \\[9pt]  &= \frac{1}{4} \big( 2 e^{iu} e^{iv} + 2 e^{-iu} e^{-iv} \big) \\[9pt]  &= \frac{1}{4} \big( 2e^{iu}e^{iv} + e^{-iu}e^{iv} - e^{-iu}e^{iv} + e^{iu}e^{-iv} - e^{iu}e^{-iv} + 2 e^{-iu}e^{-iv} \big) \\[9pt]  &= \frac{1}{4} \big( e^{iu}(e^{iv} + e^{-iv}) + e^{-iu}(e^{iv} + e^{-iv}) + e^{iu}(e^{iv} - e^{-iv}) - e^{-iu}(e^{iv} - e^{-iv}) \big) \\[9pt]  &= \frac{1}{4} \big( (e^{iu} + e^{-iu})(e^{iv} + e^{-iv}) \big) + \frac{1}{4} \big( (e^{iu} - e^{-iu})(e^{iv} - e^{-iv})\big) \\[9pt]  &= \cos u \cos v - \frac{1}{4i^2} \big( (e^{iu} - e^{-iu})(e^{iv} - e^{-iv})\big)\\[9pt]  &= \cos u \cos v - \sin u \sin v. \qquad \blacksquare \end{align*}

  3. Proof. We compute

        \begin{align*}  \sin^2 z + \cos^2 z &= \left( \frac{1}{2i} \right)^2 (e^z - e^{-z})^2 + \left( \frac{1}{2} \right)^2 (e^z + e^{-z})^2 \\[9pt]  &= -\frac{1}{4} (e^z - e^{-z})^2 + \frac{1}{4}(e^z + e^{-z})^2 \\[9pt]  &= \frac{1}{4} \left( (e^z+e^{-z})^2 - (e^z - e^{-z})^2 \right) \\[9pt]  &= \frac{1}{4} \left( (e^z + e^{-z} + e^z - e^{-z})(e^z + e^{-z} - e^z + e^{-z}) \right) \\[9pt]  &= \frac{1}{4} \left( (2e^z)(2e^{-z}) \right) \\[9pt]  &= 1. \qquad \blacksquare \end{align*}

  4. Proof. The two computations are as follows,

        \begin{align*}  \cos(iy) &= \frac{1}{2} \big( e^{i(iy)} + e^{-i(iy)} \big) \\[9pt]  &= \frac{1}{2}(e^{-y} + e^y) \\[9pt]  &= \frac{1}{2}(e^y + e^{-y}) \\[9pt]  &= \cosh y. \\[9pt]  \sin (iy) &= \frac{1}{2i} \big( e^{i(iy)} - e^{-i(iy)} \big) \\[9pt]  &= \frac{1}{2i} (e^{-y} - e^y) \\[9pt]  &= -\frac{1}{2i} (e^y - e^{-y}) \\[9pt]  &= i \sinh y. \qquad \blacksquare \end{align*}

  5. Proof. We have,

        \[ \cos z = \cos (x+iy) = \cos x \cos (iy) - \sin x \sin (iy) = \cos x \cosh y - i \sin x \sinh y. \qquad \blacksquare \]

  6. Proof. We have,

        \[ \sin z = \sin(x+iy) = \sin x \cos (iy) + \cos x \sin (iy) = \sin x \cosh y + i \cos x \sinh y. \qquad \blacksquare \]

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):